2022
DOI: 10.1101/2022.04.12.488047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge-graph-based cell-cell communication inference for spatially resolved transcriptomic data with SpaTalk

Abstract: Spatially resolved transcriptomics (ST) provides genetic information in space toward elucidation of the spatial architecture in intact organs and the spatially resolved cell-cell communications mediating tissue homeostasis, development, and disease. To facilitate inference of spatially resolved cell-cell communications from ST data, we here present SpaTalk, which relies on a graph network and knowledge graph to model and score the ligand-receptor-target signaling network between spatially proximal cells, decom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…1F), despite the data being generated by a different model. In contrast, CellChat with 2 different parameter settings [4], Giotto [17], and SpaTalk [20] failed to control false positives, possibly due to the lack of effective modelling of spatial information.…”
Section: Resultsmentioning
confidence: 99%
“…1F), despite the data being generated by a different model. In contrast, CellChat with 2 different parameter settings [4], Giotto [17], and SpaTalk [20] failed to control false positives, possibly due to the lack of effective modelling of spatial information.…”
Section: Resultsmentioning
confidence: 99%
“…We identified three recent or widely used tools that offer analysis at the multicellular resolution: stLearn (13), CellPhoneDB (10), and SpaTalk (14). We compared these tools with BulkSignalR using three human datasets: the previously used TNBC dataset (36), a HER2+ breast cancer dataset (41), and a dorsolateral prefrontal cortex dataset (42).…”
Section: Resultsmentioning
confidence: 99%
“…By simply adjusting few parameters, we found that BulkSignalR could be used for multicellular resolution spatial analyses successfully. We then compared the performance of BulkSignalR and of three tools for multicellular resolution analyses, CellPhoneDB (10), stLearn (13), and SpaTalk (14).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the transcriptional heterogeneity within the tissue from the perspective of single-cell spatial resolution and full gene coverage is an essential direction for the development in the field of biological sciences 1, 56 . The spatial locations of cells may determine their identity and how they interplay with each other in the microenvironment 57, 58 . However, there are many technical challenges, and thus, such a technology has not been fully realized yet.…”
Section: Discussionmentioning
confidence: 99%